The complete mitochondrial genome of a Chinese endemic species, Paraprenanthes diversifolia (Vaniot) N. Kilian (Cichorieae; Asteraceae) - Shuoming Fu; Ran Chu; Xin Xu; Haoyuan Chen; Yuhua Shi; Shixin Zhu; Zhen Wei (Mitochondrial DNA. Part B. Resources, 2020)
The first complete mitochondrial genome (mt) of Paraprenanthes diversifolia (Vaniot) N. Kilian (Cichorieae; Asteraceae) was sequenced and successfully assembled in this study. The full length of the mt genome is 360,751 bp, containing 73 genes (33 protein-coding genes, 29 tRNA genes, 6 rRNA genes, and 5 protein-coding genes containing internal stop codons). There are two pairs of long (over 1000 bp) repeat regions in the mt genome of P. diversifolia. The phylogenetic analysis indicated that P. diversifolia has a close relationship with other Lactucinae species.